Preparation process and application of aluminum alloy material
By using composite filter plates and microalloyed elements, the limitations of aluminum alloy materials in mechanical properties and corrosion resistance are solved, and high-purity and high-performance aluminum alloy materials are achieved, which meets the high-performance aluminum alloy materials in automobiles and other industries. demand in the field.
Patent Information
- Application Number
- CN202411551312.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-11-01
AI Technical Summary
Traditional aluminum alloy materials have limitations in terms of mechanical properties and corrosion resistance, especially in high temperatures, and inclusions and pores are easily generated during smelting and casting, which affects the performance and service life of the material.
Using specific composite filter plates and microalloyed elements, the composite filter plates remove non-metallic inclusions and gases in the aluminum alloy melt, combined with optimized heat treatment processes and rare earth element additions, the purity and mechanical properties of the aluminum alloy are improved.
It significantly improves the purity and mechanical properties of aluminum alloy materials, enhances corrosion resistance and compressive strength, and meets the needs of high-performance aluminum alloy materials in automobiles and other fields.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aluminum alloys, and in particular to a preparation process of an aluminum alloy material and application thereof. Background Art
[0002] With the rapid development of modern industry, the requirements for material performance are increasing day by day, especially in the fields of aerospace, automobile manufacturing, rail transportation, etc., the demand for lightweight, high-strength, and corrosion-resistant aluminum alloy materials is growing. Aluminum alloy has become an indispensable key material in these fields due to its low density, high strength, good processing performance and excellent corrosion resistance.
[0003] However, traditional aluminum alloy materials have certain limitations in terms of mechanical properties and corrosion resistance. For example, the strength and corrosion resistance of aluminum alloys at high temperatures are often insufficient to meet increasingly stringent application requirements. In addition, aluminum alloys are prone to inclusions and pores during the smelting and casting process, and these defects can seriously affect the mechanical properties and service life of the material. Therefore, the development of new aluminum alloy materials and their preparation processes to improve their comprehensive performance has become a research hotspot in the field of materials science.
[0004] In the preparation process of aluminum alloy materials, smelting and filtration are crucial steps. Traditional filtration methods, such as using a single-layer ceramic filter plate or simple physical filtration, often fail to effectively remove non-metallic inclusions and gases from aluminum alloy melts, resulting in poor performance of the final product. In addition, the stability and mechanical strength of existing filter materials at high temperatures are not sufficient to meet the needs of high-performance aluminum alloy material preparation.
[0005] In order to solve these problems, researchers have conducted a lot of research and exploration to seek more effective filtration technology and materials. For example, by introducing micro-alloying elements, improving heat treatment processes, and adopting new filter media, the mechanical properties and corrosion resistance of aluminum alloys can be improved. Although these studies have made some progress, further research and development is still needed to achieve a comprehensive improvement in the performance of aluminum alloy materials.
[0006] Chinese invention patent CN114921698A discloses a low coarse grained aluminum alloy profile and a preparation method thereof; the low coarse grained aluminum alloy profile, by weight percentage, comprises: 0.62% to 0.68% silicon, 0.81% to 1.13% manganese, 1.37% to 1.46% magnesium, 0.73% to 0.91% iron, 0.17% to 0.35% chromium, 0.11% to 0.21% titanium, 0.07% to 0.13% copper, 0.12% to 0 .27% zinc, 0.08%~0.15% tin, 0.1%~0.25% vanadium, 0.09%~0.18% barium and the balance aluminum; the aluminum alloy profile of the invention improves the cutting performance of the aluminum alloy profile by selecting suitable metal raw materials, and inhibits the grain growth phenomenon generated during the extrusion process of the aluminum alloy profile; the preparation method of the invention cooperates with the raw materials to reduce the coarse grain ring generated during the extrusion process of the aluminum profile and improve the quality of the aluminum profile. However, the mechanical properties and corrosion resistance of the prepared aluminum alloy profile still need to be improved. Summary of the invention
[0007] In view of the above problems, the present invention aims to provide a new aluminum alloy material preparation process, which effectively removes non-metallic inclusions and gases in the aluminum alloy melt by using a specific composite filter plate, thereby significantly improving the purity and quality of the aluminum alloy.
[0008] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions: A preparation process of an aluminum alloy material is as follows, in parts by weight: Step 1, adding 970-980 parts of aluminum ingots into a smelting furnace, setting the temperature of the smelting furnace at 650-800°C, and when the charge temperature rises to the set value and begins to melt, sequentially adding 1-3 parts of iron, 0.8-1.2 parts of manganese and 0.8-1.2 parts of chromium powder, and then adding 8-10 parts of magnesium ingots, 0.5-1 parts of zinc ingots, 0.8-1.2 parts of titanium ingots, 2-3 parts of copper ingots and 4-6 parts of polysilicon, and finally adding 0.1-0.3 parts of gadolinium, 0.2-0.4 parts of lanthanum ingots, 0.2-0.4 parts of cerium ingots, and 0.1-0.3 parts of praseodymium ingots, stirring evenly until the materials are completely melted to obtain an alloy solution; Step 2, filtering the alloy solution obtained in step 1 using a composite filter plate to obtain a stand-by solution; Step 3, casting the standby liquid prepared in step 2 into an aluminum rod, and then leaving it to stand to cast it into a billet; Step 4, placing the blank prepared in step 3 in a homogenization treatment device; keeping the blank warm; performing homogenization treatment to obtain a homogenized aluminum alloy ingot; Step 5, extruding the aluminum alloy ingot prepared in step 4 in an extruder to obtain a 6 series modified alloy profile; Step 6, subjecting the 6 series modified alloy profile prepared in step 5 to online solution quenching treatment, the treatment temperature is 500-560°C, the online quenching device realizes three cooling methods of strong wind, spraying, and water, and then performs aging treatment to obtain T6 state aluminum alloy; Step 7, stretching and straightening the T6 aluminum alloy prepared in step 6, with a stretching amount of 1-5%, to obtain an aluminum alloy material; The preparation method of the composite filter plate is as follows, in parts by weight: S1, 70-90 parts of boron carbide, 70-90 parts of illite, 80-120 parts of lithium feldspar, 40-60 parts of bentonite, 80-120 parts of aluminum hydroxide, 400-600 parts of black corundum, 15-25 parts of mica powder, and 15-25 parts of quartz powder are mixed and ball-milled, and two-level particle size composite powders are screened out, and the particle sizes are 40-90 μm and 1-30 μm, respectively. 80-120 parts of composite powders of different particle sizes are respectively mixed with 30-50 parts of water, 15-25 parts of phosphoric acid, 0.5-2 parts of sodium carboxymethyl cellulose, and 0.4-0.6 parts of zinc stearate to obtain large-particle size ceramic slurry and small-particle size ceramic slurry; S2, immersing the polyurethane foam in the large-particle ceramic slurry for 5 to 15 minutes, taking out the foam, and pressing the excess slurry with a roller press to obtain a combined foam; S3, placing the combined foam body in a vacuum drying oven, drying at 90-100° C. for 10-20 minutes, pouring a small-particle ceramic slurry on the combined foam body, and after the slurry stops flowing out, squeezing out the excess slurry with a roller press, transferring the slurry to a drying oven for 10-20 minutes, and repeating the pouring and drying operation 1-3 times to obtain a preform; S4. Dry the preform at 100-130°C for 4-6 hours, transfer it into a kiln, heat it to 300-500°C at a rate of 1-3°C / min, keep it at that temperature for 0.5-2 hours, continue to heat it to 1400-1500°C at a rate of 1-3°C / min, keep it at that temperature for 1-3 hours, then cool it to room temperature naturally, cut it, and grind it to obtain a composite filter plate.
[0009] In the step 3, the mixture is allowed to stand at 660-770° C. for 0.5-2 hours.
[0010] In step 4, the temperature is kept at 530-580° C. for 6-8 hours.
[0011] In the extrusion molding process in step 5, the aluminum alloy ingot is heated to 500-560°C, the temperature gradient is 6-8°C, the extrusion barrel temperature is 400-450°C, the extrusion die temperature is 460-500°C, and the extrusion speed is 4-6m / min.
[0012] The polyurethane foam is a modified polyurethane foam.
[0013] The preparation method of the modified polyurethane foam is as follows, in parts by weight: 10-30 parts of polyoxyethyl glycerol ether and 10-30 parts of polytetramethylene glycol, 50-70 parts of polyethylene glycol, 1-3 parts of water, 0.4-0.6 parts of di-n-butyltin diisooctanoate and 0.8-1.2 parts of hydroxy silicone oil are mixed in a beaker, and stirred at 30-50°C for 4-6 minutes to form a uniform mixed solution. 8-12 parts of sodium polyacrylate and 25-35 parts of 1,6-hexamethylene diisocyanate are quickly added to the mixed solution, and the solution is poured into a pre-prepared mold to ensure that the foam completely fills the space in the mold. Stirring is started, and then the mixture is allowed to stand for 8-12 minutes. The filled mold is placed in an oven at 80-120°C for 1-3 hours of curing treatment, and then taken out, cooled and demolded to obtain a modified polyurethane foam. The size of the modified polyurethane foam is 300-400×300-400×20-80mm.
[0014] The aluminum alloy material is used in automobile accessories.
[0015] Preferably, the aluminum alloy material is used in a sunroof motor, an instrument panel or a battery tray.
[0016] In the aluminum alloy material preparation process of the present invention, the functions of various substances are as follows: Aluminum ingots, as the main raw material of aluminum alloy, provide aluminum elements and are the basis of aluminum alloy.
[0017] Elements such as silicon, iron, copper, manganese, magnesium, chromium, zinc and titanium are added as alloying elements in specific chemical composition ratios to improve the mechanical properties, corrosion resistance and processing properties of aluminum alloys.
[0018] Rare earth elements such as gadolinium, lanthanum, cerium and praseodymium, as microalloying elements, can refine the grains of aluminum alloys and improve the strength and toughness of the alloys.
[0019] The composite filter plate is used to filter impurities and non-metallic inclusions in the alloy solution to improve the purity and performance of the aluminum alloy.
[0020] Boron carbide is used as hard particles in the composite filter plate to improve the wear resistance and hardness of the filter plate.
[0021] Illite is an aluminum-containing silicate mineral used in the preparation of composite filter plates to improve the chemical stability of the filter plates.
[0022] Lithium feldspar provides the aluminosilicate component in the composite filter plate and helps form the skeleton structure of the filter plate.
[0023] Aluminum hydroxide aids in the bonding and sintering of the particles.
[0024] Black corundum provides high hardness and wear resistance in composite filter plates.
[0025] Mica powder and quartz powder are used as filling materials in the composite filter plate to adjust the porosity and strength of the filter plate.
[0026] Phosphoric acid aids in the bonding and sintering of the particles.
[0027] Sodium carboxymethyl cellulose and zinc stearate are used as additives in the preparation of composite filter plates to improve the rheological properties of the slurry and enhance the mechanical strength of the filter plates.
[0028] In the method for preparing the modified polyurethane foam of the present invention, the functions of the various substances are as follows: Polyethylene glycol, as another polyol, also participates in the reaction with isocyanate, affecting the physical properties of the foam and increasing the flexibility and elongation of the foam.
[0029] In the preparation of polyurethane foam, the role of water is to react with isocyanate to generate carbon dioxide gas. This gas acts as a foaming agent in the foam formation process, forming the porous structure of the foam.
[0030] Di-n-butyltin diisooctanoate is a catalyst used to accelerate the polymerization reaction between isocyanate and polyol, increase the reaction rate, and thus affect the speed and quality of foam formation.
[0031] Hydroxy silicone oil is usually used as a surfactant to help improve the surface properties of the foam, reduce surface defects, and improve the uniformity and stability of the foam.
[0032] As a high molecular compound, sodium polyacrylate plays a reinforcing role in foam and can improve the mechanical strength and stability of the foam.
[0033] 1,6-Hexanediisocyanate is a type of isocyanate and another key raw material for the preparation of polyurethane foam. It reacts with polyols to form polyurethane, forming the hard segment of the foam, providing mechanical strength and thermal stability of the foam.
[0034] Polyoxyethyl glycerol ether is a nonionic surfactant with good water solubility, dispersibility and emulsification. When it is compounded with polytetramethylene ether, it can form a more uniform and dense foam structure, thereby improving the mechanical strength and chemical stability of the modified polyurethane foam. Polytetramethylene ether itself is a high molecular weight polyether, known for its excellent flexibility and elasticity, and is often used to prepare high-performance polyurethane materials. The introduction of polytetramethylene ether enhances the elasticity and compression resistance of the foam, which is critical for maintaining the structural integrity of the filter plate. This compounding may also improve the pore structure of the foam, allowing the ceramic slurry to form a more uniform and dense coating on the surface of the foam, thereby improving the compressive strength and thermal shock resistance of the filter plate. In addition, the addition of polyoxyethyl glycerol ether may also enhance the wettability of the foam, allowing the ceramic slurry to be more evenly coated on the surface of the foam, further enhancing the uniformity and density of the coating. On the whole, the compounding of polyoxyethyl glycerol ether and polytetramethylene furan ether not only improves the physical properties of the modified polyurethane foam, but also enhances its chemical stability and wettability. These factors work together to improve the performance of the composite filter plate, thereby improving the mechanical properties of the aluminum alloy material.
[0035] The combination and interaction of these substances enable the aluminum alloy material preparation process to produce aluminum alloy products with excellent properties. By precisely controlling the proportions of these substances and the processing technology, the properties of aluminum alloys can be optimized to meet specific industrial application requirements.
[0036] Compared with the prior art, it has the following beneficial effects: 1) The present invention uses a special composite filter plate and introduces rare earth elements. The preparation process of the present invention effectively removes inclusions and gases in the aluminum alloy melt, thereby improving the purity of the aluminum alloy and enhancing the tensile properties and fracture toughness of the material.
[0037] 2) The optimized heat treatment process and the addition of micro-alloying elements in the present invention improve the corrosion resistance of the aluminum alloy, making it more suitable for application fields requiring high corrosion resistance such as automotive parts.
[0038] 3) The use of the modified polyurethane foam of the present invention and the specific composite filter plate preparation process make the filter plate have higher compressive strength and thermal shock resistance, so that it is more effective in filtering aluminum alloy melt, further improving the comprehensive performance of aluminum alloy materials. DETAILED DESCRIPTION
[0039] Main sources of substances: Commercially available polyurethane foam: thermal conductivity (normal temperature): 0.035, grade: B1, elongation at break: 11%, specification: 350×350×50mm.
[0040] Polyoxyethyl glyceryl ether: average molecular weight 850.
[0041] Polyethylene glycol: average molecular weight 600, average hydroxyl value 192.
[0042] Sodium polyacrylate, average molecular weight is 1500.
[0043] Polytetramethylenetetrahydrofuran ether, average molecular weight is 1000.
[0044] Polyether 210, average hydroxyl value 110 mgKOH / g.
[0045] Tetrameric 1,2-propylene glycol, average molecular weight 250.
[0046] Trihydroxy polyoxypropylene ether, average molecular weight 3000.
[0047] The remaining raw materials in the examples and comparative examples of the present invention are all commercially available products.
[0048] The design idea of the present invention is to provide a new type of aluminum alloy material preparation process. By using a composite filter plate containing specific components, non-metallic inclusions and gases in the aluminum alloy melt can be effectively removed, thereby improving the purity and quality of the aluminum alloy. At the same time, rare earth elements are introduced for micro-alloying, and specific heat treatment and processing techniques are used to obtain aluminum alloy materials with excellent mechanical properties and corrosion resistance, thereby meeting the demand for high-performance aluminum alloy materials in fields such as automobile manufacturing. Example 1
[0049] A preparation process of an aluminum alloy material is as follows: Step 1, add 976.7kg aluminum ingot into the smelting furnace, set the temperature of the smelting furnace at 700°C, when the charge temperature rises to the set value and starts to melt, add 2kg iron, 1kg manganese and 1kg chromium powder in turn, continue to add 9kg magnesium ingot, 0.8kg zinc ingot, 1kg titanium ingot, 2.5kg copper ingot and 5kg polysilicon, and finally add 0.2kg gadolinium, 0.3kg lanthanum ingot, 0.3kg cerium ingot, 0.2kg praseodymium ingot, stir evenly until the materials are completely melted to obtain an alloy solution; Step 2, filtering the alloy solution obtained in step 1 using a double-stage ceramic filter plate, wherein the mesh numbers of the double-stage ceramic filter plate are 40 mesh and 60 mesh respectively, and obtaining a stand-by solution after filtration; Step 3, casting the standby liquid prepared in step 2 into an aluminum rod, and then leaving it to stand at 710° C. for 1 hour to cast it into a billet; Step 4, placing the blank prepared in step 3 in a homogenization treatment device; keeping the temperature at 550° C. for 7 hours; performing homogenization treatment to obtain a homogenized aluminum alloy ingot; Step 5, extruding the aluminum alloy ingot prepared in step 4 in an extruder, during the extrusion process, the aluminum alloy ingot is heated to 530° C., the temperature gradient is 7° C., the extrusion barrel temperature is 430° C., the extrusion die temperature is 480° C., and the extrusion speed is 5 m / min, to obtain a 6 series modified alloy profile; Step 6, subjecting the 6 series modified alloy profile prepared in step 5 to online solution quenching treatment, the treatment temperature is 520° C., and the online quenching device realizes three cooling methods: strong wind, spraying, and water, and then performs aging treatment to obtain T6 state aluminum alloy; Step 7: stretch and straighten the T6 aluminum alloy prepared in step 6 with a stretching amount of 2% to obtain an aluminum alloy material. Example 2
[0050] A preparation process of an aluminum alloy material is as follows: Step 1, add 976.7kg aluminum ingot into the smelting furnace, set the temperature of the smelting furnace at 700°C, when the charge temperature rises to the set value and starts to melt, add 2kg iron, 1kg manganese and 1kg chromium powder in turn, continue to add 9kg magnesium ingot, 0.8kg zinc ingot, 1kg titanium ingot, 2.5kg copper ingot and 5kg polysilicon, and finally add 0.2kg gadolinium, 0.3kg lanthanum ingot, 0.3kg cerium ingot, 0.2kg praseodymium ingot, stir evenly until the materials are completely melted to obtain an alloy solution; Step 2, filtering the alloy solution obtained in step 1 using a composite filter plate to obtain a stand-by solution; Step 3, casting the standby liquid prepared in step 2 into an aluminum rod, and then leaving it to stand at 710° C. for 1 hour to cast it into a billet; Step 4, placing the blank prepared in step 3 in a homogenization treatment device; keeping the temperature at 550° C. for 7 hours; performing homogenization treatment to obtain a homogenized aluminum alloy ingot; Step 5, extruding the aluminum alloy ingot prepared in step 4 in an extruder, during the extrusion process, the aluminum alloy ingot is heated to 530° C., the temperature gradient is 7° C., the extrusion barrel temperature is 430° C., the extrusion die temperature is 480° C., and the extrusion speed is 5 m / min, to obtain a 6 series modified alloy profile; Step 6, subjecting the 6 series modified alloy profile prepared in step 5 to online solution quenching treatment, the treatment temperature is 520° C., and the online quenching device realizes three cooling methods: strong wind, spraying, and water, and then performs aging treatment to obtain T6 state aluminum alloy; Step 7: stretch and straighten the T6 aluminum alloy prepared in step 6 with a stretching amount of 2% to obtain an aluminum alloy material.
[0051] The preparation method of the composite filter plate is as follows: S1, 80kg boron carbide, 80kg illite, 100kg lithium feldspar, 50kg bentonite, 100kg aluminum hydroxide, 500kg black corundum, 20kg mica powder, 20kg quartz powder were mixed and ball-milled, and two-grade composite powders were screened out, with particle sizes of 60μm and 20μm, respectively. 100kg of composite powders of different particle sizes were respectively mixed with 40kg water, 20kg phosphoric acid, 1kg sodium carboxymethyl cellulose, and 0.5kg zinc stearate to obtain large-particle ceramic slurry and small-particle ceramic slurry; S2, immersing the modified polyurethane foam in the large-particle ceramic slurry for 10 minutes, taking out the foam, and pressing the excess slurry with a roller press to obtain a combined foam; S3, placing the combined foam body in a vacuum drying oven, drying at 95° C. for 20 minutes, pouring a small-particle ceramic slurry on the combined foam body, and after the slurry stops flowing out, squeezing out the excess slurry with a roller press, transferring the slurry to a drying oven for 15 minutes, and repeating the pouring and drying operation 3 times to obtain a preform; S4. Dry the preform at 120°C for 5 hours, transfer it into a kiln, heat it to 400°C at a rate of 2°C / min, keep it for 1 hour, continue to heat it to 1450°C at a rate of 2°C / min, keep it at that temperature for 2 hours, then naturally cool it to room temperature, cut it, and grind it to obtain a composite filter plate.
[0052] The preparation method of the modified polyurethane foam is as follows: Mix 40kg of polyoxyethyl glycerol ether, 60kg of polyethylene glycol, 2kg of water, 0.5kg of di-n-butyltin diisooctanoate and 1kg of hydroxy silicone oil in a beaker, stir at 40°C for 5 minutes to form a uniform mixed solution, quickly add 10kg of sodium polyacrylate and 30kg of 1,6-hexamethylene diisocyanate to the mixed solution, pour it into a pre-prepared mold, ensure that the foam completely fills the space in the mold, start stirring, and then let it stand for 10 minutes, put the filled mold into an oven at 100°C for 1.5 hours of curing treatment, then take out, cool and demold to obtain a modified polyurethane foam, the size of the modified polyurethane foam is 350×350×50mm. Example 3
[0053] The preparation process of an aluminum alloy material is basically the same as that of Example 2, the only difference being that the preparation method of the modified polyurethane foam is different.
[0054] The preparation method of the modified polyurethane foam is as follows: Mix 40kg of polyether 210, 60kg of polyethylene glycol, 2kg of water, 0.5kg of di-n-butyltin diisooctanoate and 1kg of hydroxy silicone oil in a beaker, stir at 40°C for 5 minutes to form a uniform mixed solution, quickly add 10kg of sodium polyacrylate and 30kg of 1,6-hexamethylene diisocyanate to the mixed solution, pour it into a pre-prepared mold, ensure that the foam completely fills the space in the mold, start stirring, and then let it stand for 10 minutes, put the filled mold into an oven at 100°C for 1.5 hours of curing treatment, then take it out, cool it and demold it to obtain a modified polyurethane foam, the size of the modified polyurethane foam is 350×350×50mm.
[0055] The preparation method of the composite filter plate is the same as that of Example 2. Example 4
[0056] The preparation process of an aluminum alloy material is basically the same as that of Example 2, the only difference being that the preparation method of the modified polyurethane foam is different.
[0057] The preparation method of the modified polyurethane foam is as follows: Mix 40kg of tetrapropylene glycol, 60kg of polyethylene glycol, 2kg of water, 0.5kg of di-n-butyltin diisooctanoate and 1kg of hydroxy silicone oil in a beaker, stir at 40°C for 5 minutes to form a uniform mixed solution, quickly add 10kg of sodium polyacrylate and 30kg of 1,6-hexamethylene diisocyanate to the mixed solution, pour it into a pre-prepared mold, ensure that the foam completely fills the space in the mold, start stirring, and then let it stand for 10 minutes, put the filled mold into an oven at 100°C for 1.5 hours of curing treatment, then take it out, cool it and demold it to obtain a modified polyurethane foam, the size of the modified polyurethane foam is 350×350×50mm.
[0058] The preparation method of the composite filter plate is the same as that of Example 2. Example 5
[0059] The preparation process of an aluminum alloy material is basically the same as that of Example 2, the only difference being that the preparation method of the modified polyurethane foam is different.
[0060] The preparation method of the modified polyurethane foam is as follows: 40 kg of polytetrahydrofuran ether, 60 kg of polyethylene glycol, 2 kg of water, 0.5 kg of di-n-butyltin diisooctanoate and 1 kg of hydroxy silicone oil were mixed in a beaker, and stirred at 40 ° C for 5 minutes to form a uniform mixed solution. 10 kg of sodium polyacrylate and 30 kg of 1,6-hexamethylene diisocyanate were quickly added to the mixed solution, and poured into a pre-prepared mold to ensure that the foam completely fills the space in the mold. Stirring was started, and then allowed to stand for 10 minutes. The filled mold was placed in an oven at 100 ° C for 1.5 hours of curing treatment, and then taken out for cooling and demolding to obtain a modified polyurethane foam. The size of the modified polyurethane foam is 350×350×50 mm.
[0061] The preparation method of the composite filter plate is the same as that of Example 2. Example 6
[0062] The preparation process of an aluminum alloy material is basically the same as that of Example 2, the only difference being that the preparation method of the modified polyurethane foam is different.
[0063] The preparation method of the modified polyurethane foam is as follows: Mix 20kg of polyoxyethyl glycerol ether, 20kg of polytetramethylene glycol, 60kg of polyethylene glycol, 2kg of water, 0.5kg of di-n-butyltin diisooctanoate and 1kg of hydroxy silicone oil in a beaker, stir at 40°C for 5 minutes to form a uniform mixed solution, quickly add 10kg of sodium polyacrylate and 30kg of 1,6-hexamethylene diisocyanate to the mixed solution, pour it into a pre-prepared mold, ensure that the foam completely fills the space in the mold, start stirring, then let it stand for 10 minutes, put the filled mold into an oven at 100°C for 1.5 hours of curing treatment, then take it out, cool it and demold it to obtain a modified polyurethane foam, the size of the modified polyurethane foam is 350×350×50mm.
[0064] The preparation method of the composite filter plate is the same as that of Example 2.
[0065] Comparative Example 1 The preparation process of an aluminum alloy material is basically the same as that of Example 2, the only difference being that the preparation method of the modified polyurethane foam is different.
[0066] The preparation method of the modified polyurethane foam is as follows: 40 kg of trihydroxy polyoxypropylene ether, 60 kg of polyethylene glycol, 2 kg of water, 0.5 kg of di-n-butyltin diisooctanoate and 1 kg of hydroxy silicone oil were mixed in a beaker, and stirred at 40 ° C for 5 minutes to form a uniform mixed solution. 10 kg of sodium polyacrylate and 30 kg of 1,6-hexamethylene diisocyanate were quickly added to the mixed solution, and poured into a pre-prepared mold to ensure that the foam completely fills the space in the mold. Stirring was started, and then allowed to stand for 10 minutes. The filled mold was placed in an oven at 100 ° C for 1.5 hours of curing treatment, and then taken out, cooled and demolded to obtain a modified polyurethane foam. The size of the modified polyurethane foam is 350×350×50 mm.
[0067] The preparation method of the composite filter plate is the same as that of Example 2.
[0068] Comparative Example 2 The preparation process of an aluminum alloy material is basically the same as that of Example 2, the only difference being that the modified polyurethane foam is replaced with commercially available polyurethane foam.
[0069] Test Example 1 Mechanical properties test The tensile properties of the aluminum alloy materials prepared in the embodiments and comparative examples of the present invention were tested at room temperature with reference to GB / T 16865-2023 “Specimens and methods for tensile testing of deformed aluminum, magnesium and their alloy products”; The fracture toughness test of the aluminum alloy materials prepared in the examples and comparative examples of the present invention was carried out with reference to GB / T 4161-2007 "Method for testing plane strain fracture toughness KIC of metallic materials". The test results are shown in Table 1.
[0070] Table 1
[0071] Test Example 2 The filter plates used in the above embodiments and comparative examples were tested for compressive strength at room temperature according to GB / T 4740-1999 “Test method for compressive strength of ceramic materials”.
[0072] Thermal shock resistance: Preheat the heating furnace to 800°C for 10 minutes, then move the filter plates used in the above embodiments and comparative examples into the furnace and keep them for 30 minutes. Then open the furnace door and quickly move the filter plates out of the furnace to expose them to the air for natural cooling. Repeat this process 8 times and observe whether the filter plates are cracked, ceramsite peeled off or broken.
[0073] The test results are shown in Table 2.
[0074] Table 2
[0075] It can be seen from the data in Tables 1 and 2 that the aluminum alloy material prepared in Example 6 has the best mechanical properties, and the obtained composite filter plate has excellent compressive strength and thermal shock resistance.
[0076] The composite filter plate plays a key role in the preparation process of aluminum alloy materials. It improves the purity and quality of aluminum alloy by effectively removing non-metallic inclusions and gases in the aluminum alloy melt. Specifically, the multi-layer network structure and high porosity of the composite filter plate enable the aluminum liquid to be fully filtered when it flows through the filter plate, and the inclusions are intercepted, adsorbed and deposited, thereby significantly reducing the impurity content in the aluminum alloy. This not only improves the mechanical properties and corrosion resistance of the casting, but also reduces casting defects such as pores and cracks, ultimately improving the comprehensive performance and service life of the aluminum alloy material.
[0077] Compared with commercially available polyurethane foam, modified polyurethane foam exhibits better performance in the preparation of aluminum alloy materials and composite filter plates, mainly because the surface of the modified polyurethane foam becomes rougher, providing more mechanical interlocking points, which can better grasp and hold the ceramic slurry. At the same time, the improvement in wettability means that the modified polyurethane foam can coat the ceramic slurry more evenly, so that the slurry forms a more uniform and denser coating on the surface of the foam. This uniform and dense coating helps to form a composite filter plate with higher compressive strength and thermal shock resistance. When this filter plate is used in the preparation of aluminum alloy materials, it can effectively remove more non-metallic inclusions and gases, thereby improving the purity and quality of the aluminum alloy, and ultimately resulting in better mechanical properties of the aluminum alloy material.
[0078] The aluminum alloy material prepared using polyoxyethyl glyceryl ether in Example 2 has a composite filter plate with better mechanical properties and higher compressive strength and thermal shock resistance, and the reason for this is mainly due to the characteristics of polyoxyethyl glyceryl ether. Polyoxyethyl glyceryl ether has good wettability and dispersibility, which allows the ceramic slurry to be more evenly covered on the foam surface when preparing modified polyurethane foam, forming a dense and uniform coating. In addition, polyoxyethyl glyceryl ether has high chemical stability and mechanical strength, and can provide more mechanical locking points, thereby improving the overall strength and thermal shock resistance of the composite filter plate. These advantages make the aluminum alloy material in Example 2 perform better in mechanical properties and filter plate performance.
[0079] In Example 6, the compounding of polyoxyethyl glycerol ether and polytetrahydrofuran ether significantly improved the mechanical properties of the aluminum alloy material and the compressive strength and thermal shock resistance of the composite filter plate. Polyoxyethyl glycerol ether has good wettability and dispersibility, which enables the ceramic slurry to evenly cover the foam surface to form a dense coating; polytetrahydrofuran ether enhances the mechanical strength and chemical stability of the foam. After the two are compounded, the synergistic effect significantly improves the adhesion and uniformity of the ceramic slurry, increases the mechanical interlocking points, and finally prepares a composite filter plate and aluminum alloy material with better performance.
Claims
1. A process for preparing an aluminum alloy material, comprising the following steps: melting an aluminum ingot, adding iron powder, manganese powder and chromium powder in sequence, continuing to add magnesium ingot, zinc ingot, titanium ingot, copper ingot and polysilicon, and finally adding gadolinium ingot, lanthanum ingot, cerium ingot and praseodymium ingot, stirring evenly until the materials are completely melted to obtain an alloy solution; filtering, casting into aluminum rods, homogenizing, extruding, quenching, and stretching and straightening; characterized in that: The amount of each raw material is: 970-980 parts by weight of aluminum ingot, 1-3 parts of iron powder, 0.8-1.2 parts of manganese powder, 0.8-1.2 parts of chromium powder, 8-10 parts of magnesium ingot, 0.5-1 parts of zinc ingot, 0.8-1.2 parts of titanium ingot, 2-3 parts of copper ingot, 4-6 parts of polysilicon, 0.1-0.3 parts of gadolinium ingot, 0.2-0.4 parts of lanthanum ingot, 0.2-0.4 parts of cerium ingot, 0.1-0.3 parts of praseodymium ingot; The filtration is carried out using a composite filter plate; the preparation method of the composite filter plate is as follows, in parts by weight: S1, 70-90 parts of boron carbide, 70-90 parts of illite, 80-120 parts of lithium feldspar, 40-60 parts of bentonite, 80-120 parts of aluminum hydroxide, 400-600 parts of black corundum, 15-25 parts of mica powder, and 15-25 parts of quartz powder are mixed and ball-milled, and two-level particle size composite powders are screened out, and the particle sizes are 40-90 μm and 1-30 μm, respectively. 80-120 parts of composite powders of different particle sizes are respectively mixed with 30-50 parts of water, 15-25 parts of phosphoric acid, 0.5-2 parts of sodium carboxymethyl cellulose, and 0.4-0.6 parts of zinc stearate to obtain large-particle size ceramic slurry and small-particle size ceramic slurry; S2, immersing the modified polyurethane foam in the large-particle ceramic slurry for 5 to 15 minutes, taking out the foam, and pressing the excess slurry with a roller press to obtain a combined foam; S3, placing the combined foam body in a vacuum drying oven, drying at 90-100° C. for 10-20 minutes, pouring a small-particle ceramic slurry on the combined foam body, and after the slurry stops flowing out, squeezing out the excess slurry with a roller press, transferring the slurry to a drying oven for 10-20 minutes, and repeating the pouring and drying operation 1-3 times to obtain a preform; S4. Dry the preform at 100-130°C for 4-6 hours, transfer it into a kiln, heat it to 300-500°C at a rate of 1-3°C / min, keep it at that temperature for 0.5-2 hours, continue to heat it to 1400-1500°C at a rate of 1-3°C / min, keep it at that temperature for 1-3 hours, then cool it to room temperature naturally, cut it, and grind it to obtain a composite filter plate.
2. The process for preparing the aluminum alloy material according to claim 1, characterized in that: The aluminum rod is cast by casting the filtered aluminum alloy solution into an aluminum rod, and the aluminum rod is allowed to stand at 660-770° C. for 0.5-2 hours to obtain a billet.
3. The process for preparing the aluminum alloy material according to claim 2, characterized in that: The homogenization treatment is to keep the billet at 530-580°C for 6-8 hours to obtain an aluminum alloy ingot.
4. The process for preparing the aluminum alloy material according to claim 3, characterized in that: During the extrusion process, the aluminum alloy ingot is heated to 500~560℃, the temperature gradient is 6~8℃, the extrusion barrel temperature is 400~450℃, the extrusion die temperature is 460~500℃, and the extrusion speed is 4~6m / min.
5. The process for preparing the aluminum alloy material according to claim 1, characterized in that: The preparation method of the modified polyurethane foam is as follows, in parts by weight: 10-30 parts of polyoxyethyl glycerol ether and 10-30 parts of polytetramethylene glycol, 50-70 parts of polyethylene glycol, 1-3 parts of water, 0.4-0.6 parts of di-n-butyltin diisooctanoate and 0.8-1.2 parts of hydroxy silicone oil are mixed in a beaker, and stirred at 30-50°C for 4-6 minutes to form a uniform mixed solution. 8-12 parts of sodium polyacrylate and 25-35 parts of 1,6-hexamethylene diisocyanate are quickly added to the mixed solution, and the solution is poured into a pre-prepared mold to ensure that the foam completely fills the space in the mold. Stirring is started, and then the mixture is allowed to stand for 8-12 minutes. The filled mold is placed in an oven at 80-120°C for 1-3 hours of curing treatment, and then taken out, cooled and demolded to obtain a modified polyurethane foam. The size of the modified polyurethane foam is 300-400×300-400×20-80mm.
6. An aluminum alloy material, characterized in that: Prepared by the process described in any one of claims 1 to 5.
7. Application of the aluminum alloy material as claimed in claim 6 in automobile parts.
8. The use according to claim 7, characterized in that The automobile accessory is a sunroof motor, an instrument panel or a battery tray.
Citation Information
Patent Citations
Aluminum alloy profile with low coarse grain ring and preparation method thereof
CN114921698A
Aluminium oxide foam ceramic filter
CN101164658A
High-strength and high-tenacity aluminum alloy section for bumper and preparing method of high-strength and high-tenacity aluminum alloy profile
CN106086551A
Gradient pore silicon carbide ceramic filter plate and preparation method thereof
CN107266113A
Multi-cavity high-strength 6061 aluminium alloy applicable to automobile threshold and preparation method thereof
CN110306085A
